Trajectories of body mass index and risk of incident hypertension among a normal body mass index population: A prospective cohort study - Jiahui Xu; Rui Zhang; Rongrong Guo; Yali Wang; Yue Dai; Yanxia Xie; Jia Zheng; Zhaoqing Sun; Liying Xing; Yingxian Sun; Liqiang Zheng (The Journal of Clinical Hypertension, 2021)
Abstract It is unclear whether there are different body mass index (BMI) trajectories among a population with normal BMI levels, and the association between BMI patterns and incident hypertension is not well characterized. This prospective cohort study includes surveys conducted at baseline and three follow‐ups. 3939 participants who are free of hypertension at baseline or first two follow‐ups were enrolled. At baseline, the age of participants ranged from 35 to 82 years and the mean age was 45.9 years. The BMI trajectories were identified using latent mixture modeling with data from the baseline and first two follow‐ups. The effects of different BMI trajectories on the development of hypertension were analyzed using a Cox proportional hazard model. Four distinct BMI trajectories were identified over the study period (2004‐2010): normal‐stable (n = 1456), normal‐increasing (n = 2159), normal‐fluctuated (n = 166), and normal‐sharp‐increasing (n = 158). Relative to the normal‐stable BMI group, the hazard ratios (HRs) and 95% confidence intervals (CIs) after adjustment for confounding factors of the normal‐increasing, normal‐fluctuated, and normal‐sharp‐increasing groups were 1.244 (1.103‐1.402), 1.331 (1.008‐1.756), and 1.641 (1.257‐2.142), respectively. Additionally, subgroup analysis showed that the normal‐fluctuated BMI trajectory was associated with a significantly higher risk of hypertension only in women (HR = 1.362; 95% CI = 1.151‐1.611). The BMI trajectories were significant predictors of hypertension incidence, and increasing BMI trajectories within the currently designated normal range were associated with an increased hypertension risk, especially in women.